Investigation of cationicity and structure of pseudin-2 analogues for enhanced bacterial selectivity and anti-inflammatory activity - Dasom Jeon (Nature Portfolio, 2017)
Abstract Pseudin-2 (Ps), isolated from the frog Pseudis paradoxa, exhibits potent antibacterial activity and cytotoxicity. To develop antimicrobial peptides with anti-inflammatory activity and low cytotoxicity, we designed Ps analogues with Lys substitutions, resulting in elevated amphipathic α-helical structure and cationicity. We further substituted Gly11 with Pro (Ps-P analogues) to increase bacterial cell selectivity. Ps analogues retained antimicrobial activity and exhibited reduced cytotoxicity, whereas Ps-P analogues exhibited lower cytotoxicity and antimicrobial activity. Tertiary structures revealed that Ps has a linear α-helix from Leu2 to Glu24, whereas Ps-P has a bend at Pro11 between two short α-helixes. Using various biophysical experiments, we found that Ps analogues produced much higher membrane depolarization than Ps-P analogues, whereas Ps-P analogues may penetrate bacterial cell membranes. Ps and its analogue Ps-K18 exhibited potent anti-inflammatory activity in LPS-stimulated RAW264.7 and mouse dendritic cells via a mechanism involving the Toll-like receptor 4 (TLR4) pathway. These activities may arise from their direct inhibition of the formation of TLR4-MD-2_LPS complex, implying that amphipathic α-helical structure with an optimum balance between enhanced cationicity and hydrophobicity may be essential for their anti-inflammatory activity. The bent structure provided by Pro substitution plays an important role in enhancing bacterial cell selectivity and cell penetration.